(untitled) (The Pakistan Development Review, 2010)
Corporate Governance refers to the way an organisation is directed, administrated or controlled. It includes the set of rules and regulations that affect the manager’s decision and contribute to the way company is perceived by the current and potential stakeholders. The corporate governance structure specifies the distribution of rights and responsibilities among different participants in the corporation such as; boards, managers, shareholders and other stakeholders and spells out the rules and procedures and also decision-making assistance on corporate affairs. By doing this, it also provides the structure through which the company’s objectives are set and the means of obtaining those objectives and monitoring performance. Corporate governance may be the ways of bringing the interests of investors and managers into line and ensuring that firms are run for the benefit of investors.